2022
DOI: 10.1186/s12877-022-03212-2
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ perspectives of mobile X-ray services in support of healthcare-in-place in residential aged care facilities: a qualitative study

Abstract: Background Mobile X-ray services (MXS) could be used to investigate clinical issues in aged care residents within familiar surroundings, reducing transfers to and from emergency departments and enabling healthcare to be delivered in residential aged care facilities. There is however little research exploring consumer perspectives about such services. The objective of this research was to explore the perspectives and preferences of residents about the provision of MXS in residential aged care fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…A 2015 evaluation of MXS delivered by one Australian hospital to residents in RACFs demonstrated a 12% reduction in emergency department (ED) presentations 5 . Our recent qualitative research from the perspective of residents 6 and informal carers of residents (IC) 7 revealed strong support for using MXS in RACFs to achieve healthcare‐in‐place, concurring with the perspectives of health and aged care clinicians and managers (stakeholders) 8,9 …”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…A 2015 evaluation of MXS delivered by one Australian hospital to residents in RACFs demonstrated a 12% reduction in emergency department (ED) presentations 5 . Our recent qualitative research from the perspective of residents 6 and informal carers of residents (IC) 7 revealed strong support for using MXS in RACFs to achieve healthcare‐in‐place, concurring with the perspectives of health and aged care clinicians and managers (stakeholders) 8,9 …”
Section: Introductionmentioning
confidence: 66%
“…Stakeholders also observed this. This negates the policy aim of the Medicare call‐out rebate of promoting healthcare‐in‐place and reducing avoidable ED presentations, 19 and is counter to the preferences of many residents and IC to avoid transfer if possible 6,7 . Substituting ‘free’ services in response to avoiding an upfront cost with an out‐of‐pocket cost remaining to the resident after they receive their Medicare rebate has also been noted in other settings, 21 and are unlikely to be utilised equitably among residents, 21 many of whom have limited income with little money for ‘extras’.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations